1958
DOI: 10.1071/ph580273
|View full text |Cite
|
Sign up to set email alerts
|

Photoneutrons from Natural Magnesium

Abstract: Recent experiments on photoneutron production from natural magnesium have produced contradictory results. Katz et al. (1954) have used brems-strahlung from a 22 MeV betatron to irradiate a natural magnesium target. The emitted neutrons were detected with boron trifluoride (BF3) counters placed in a paraffin block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1965
1965
1973
1973

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…This measurement showed much fine fragmentation of the split dipole resonance (see Fig. l(b)) and so represented a considerable departure from previous results (Fuller and Weiss 1958;Spicer et al 1958;Bramblett et al 1963;Bergere et al 1968), which were unanimous in their findings that the split giant resonance contained little or no evidence of fine fragmentation. It therefore seemed worth while to extend our attention to the dipole resonance, in the hope that some light could be shed upon this disagreement.…”
Section: Introductioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This measurement showed much fine fragmentation of the split dipole resonance (see Fig. l(b)) and so represented a considerable departure from previous results (Fuller and Weiss 1958;Spicer et al 1958;Bramblett et al 1963;Bergere et al 1968), which were unanimous in their findings that the split giant resonance contained little or no evidence of fine fragmentation. It therefore seemed worth while to extend our attention to the dipole resonance, in the hope that some light could be shed upon this disagreement.…”
Section: Introductioncontrasting
confidence: 76%
“…Although prior measurements of the 181Ta photoneutron cross section by Fuller and Weiss (1958), Spicer et al (1958), Bramblett et al (1963), andBergere et al (1968) have established the splitting of the dipole peak, it was not until the recent publication of a measurement by Ishkhanov et al (1969) that serious proposals of additional structure were made. As shown in Figure 1(b), Ishkhanov and his co-authors found that the photoabsorption cross section below 17 MeV contained a series of fine resonances of widths 0•3-0•5 Me V whilst, at higher excitations, broader structure was seen to exist.…”
Section: (A) Comparison With Other Measurementsmentioning
confidence: 99%